2014
DOI: 10.1161/circulationaha.114.010757
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 as a Treatment Target in Pulmonary Arterial Hypertension

Abstract: Background Pulmonary arterial hypertension (PH), whether idiopathic or related to underlying diseases such as HIV infection, results from complex vessel remodeling involving both pulmonary-artery smooth muscle cell (PA-SMC) proliferation and inflammation. CCR5, a co-receptor for cellular HIV-1 entry expressed on macrophages and vascular cells, may be involved in the pathogenesis of PH. Maraviroc is a new CCR5 antagonist designed to block HIV entry. Methods and Results Marked CCR5 expression was found in lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…While, our flow cytometry techniques cannot distinguish whether the increase in CD11b hi interstitial macrophages comprises interstitial, perivascular, or peri-bronchoalveolar macrophages, our complimentary histological findings argue in favor of these macrophages being mostly perivascular. Our findings are in line with and further extend previous observations by Amsellem et al who also reported no change in total lung macrophages but increased F4/80+ perivascular macrophages after 18 days of hypoxia in mice (4). Although we did not perform lineage tracing experiments, the increased numbers of perivascular macrophages are likely due to the recruitment of circulating cells and not local proliferation (3, 17).…”
Section: Discussionsupporting
confidence: 94%
“…While, our flow cytometry techniques cannot distinguish whether the increase in CD11b hi interstitial macrophages comprises interstitial, perivascular, or peri-bronchoalveolar macrophages, our complimentary histological findings argue in favor of these macrophages being mostly perivascular. Our findings are in line with and further extend previous observations by Amsellem et al who also reported no change in total lung macrophages but increased F4/80+ perivascular macrophages after 18 days of hypoxia in mice (4). Although we did not perform lineage tracing experiments, the increased numbers of perivascular macrophages are likely due to the recruitment of circulating cells and not local proliferation (3, 17).…”
Section: Discussionsupporting
confidence: 94%
“…CCR5 is strongly expressed in principal cell types implicated in PH progression, including ECs, SMCs, T cells, and macrophages [115][116][117][118][119][120][121][122]. It is considered a therapeutic target in human immunodeficiency virus (HIV) infection because it is a co-receptor for HIV cell entry [120,122].…”
Section: G-protein-coupled Receptor Ccr5mentioning
confidence: 99%
“…Notably, CCR5 expression is more marked in areas characterized by greater severity of vascular medial hypertrophy. The activation of CCR5 leads to the proliferation of cultured human PASMCs, while a human CCR5 antagonist developed as an HIV therapeutic, maraviroc, inhibits this proliferation [115]. It is reported that CCR5-deficient mice developed less severe PH than wild-type mice after hypoxia exposure, and maraviroc treatment markedly attenuated hypoxia-induced PH development (distal pulmonary artery muscularization) in CCR5 knock-in mice [122].…”
Section: G-protein-coupled Receptor Ccr5mentioning
confidence: 99%
“…[2] Besides HIV infection, CCR5 has been involved in a large number of disorders as described by epidemiological, clinical or basic studies. So, there are good evidences that linked CCR5 to liver diseases (e.g., hepatocellular carcinoma and liver steatosis), [3][4][5][6] autoimmune disorders (e.g., rheumatoid arthritis), [7] pulmonary diseases (e.g., pulmonary arterial hypertension and sarcoidosis), [8,9] organ rejection (e.g., stem cell transplant), [10] malignancies (e.g., colorectal cancer), [11] and vascular diseases (e.g., endothelial dysfunction and atherogenesis). [12,13] Therefore, we wonder if CCR5 antagonist could be an attractive therapeutic option to prevent and/or treat different inflammatory and/or malignant diseases.…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%
“…In this regard, interesting data have been obtained with MVC from studies using murine models designed to prevent liver cancer [5] or nonalcoholic fatty liver disease, [6] or treating atherogenesis, [13] or pulmonary arterial hypertension, [9] were also very relevant because this drug was effective preventing the rejection. [22] Nonetheless, not always the use of MVC supports its use as a therapeutic strategy.…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%